Costs of Allogeneic Hematopoietic Cell Transplantation Using Reduced Intensity Conditioning Regimens. (5th May 2014) - Khera, Nandita; Emmert, Amy; Storer, Barry E.; Sandmaier, Brenda M.; Alyea, Edwin P.; Lee, Stephanie J.
Abstract : Reduced intensity conditioning (RIC) regimens have allowed older patients and those with comorbidities to receive hematopoietic cell transplantation (HCT). We analyzed medical costs from the beginning of conditioning to 100 days after HCT for 484 patients and up to 2 years for 311 patients who underwent a RIC HCT at two institutions from January 2008 to December 2010. Multiple linear regression was used to analyze the association between clinical variables, center effect, and costs. Patient and transplant characteristics were comparable between the sites, although differences were seen in pretransplant performance scores. Significant predictors for lower costs for the first 100 days included a diagnosis of lymphoma/myeloma and use of human leukocyte antigen‐matched related donors. Grade II‐IV acute graft‐versus‐host disease (GVHD) was associated with higher costs. The overall short‐term costs between the two institutions were comparable when adjusted for clinical variables ( p = .43). Late costs between 100 days and 2 years after HCT were available for one cohort ( n = 311); median costs during this period were $39, 000 and accounted for 39% of costs during the first 2 years. Late costs were not associated with any pretransplant variables, but were higher with extensive chronic GVHD and death. After adjustment for clinical characteristics, the overall costs of the RIC transplants were similar between the two institutions despite different management approaches (inpatient vs. outpatient conditioning) and accounting methodologies. Use of unrelated/alternative donors, transplant for diseases other than lymphoma or myeloma, and acute GVHD were predictors for higher early costs, and extensive chronic GVHD and death were associated with higher late costs. Abstract : This study from two large centers describes the profile and predictors of costs of reduced intensity conditioning hematopoietic cell transplantation. Results indicate comparable costs between two centers with different practice patterns. Identification of optimum donors with favorable cost‐benefit ratio and interventions to prevent complications such as graft‐versus‐host disease may yield clinical and financial benefits. The study also underscores the need for collection of resource utilization data in a prospective fashion with clinical studies.